Recovering the Roots of Civil Society in Nepal - Dahal, Dev Raj (New Angle: Nepal Journal of Social Science and Public Policy, 2012)
This paper is an essay about civic values or ‘virtues’, and the need for civic education in contemporary Nepal. It makes an argument for ‘recovering the roots of civil society inNepal’, which the author locates first and foremost in Hindu philosophy. This is necessary as, in its current form, mainstream or ‘elite’ civil society has lost touch with democratic values and the sense of social responsibility that the author refers to as ‘niskam karma’. Divided along political party lines and moved by the pursuit of profit and self-promotion, ‘elite’ civil society has hampered rather than facilitated, progress towards the creation of a modern state in Nepal. Civic education programmes grounded in age-old philosophical traditions in Nepal has the potential to transform current political culture and go some way towards resolving many of Nepal’s present ills.